Does student performance in introductory economics and business courses impact ETS scores? - Peter J. Nigro; Laura Beaudin; David C. Ketcham; Michael Roberto (Journal of Business and Economic Studies (JBES), 2021)
This study examines the impact of economics education on student performance on the Educational Testing Service Major Field Test in Business. We demonstrate that grades in introductory microeconomics and macroeconomics courses have a positive relationship with overall exam performance as well as sub-scores in most content areas of the test. Furthermore, we use a measure of "extranormal" ability in economics and demonstrate its positive relationship to test performance. "Extranormal" ability represents the portion of course grades that cannot be explained by prior academic achievement. Finally, we show that the relationship between "extranormal" ability and exam performance is much more limited for female students than for male students.
Keywords: 330; Major Field Test in Business; MFT-B; standardized test performance; economics; gender